Encountering things design and theories of things - Boradkar, Prasad; Atzmon, Leslie 1954- (Bloomsbury, Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
Encountering Things brings together leading design scholars to explore the relationship between thing theory and design, exploring production processes and offering an engaging, theoretical perspective about the social and cultural lives of objects. Focusing on the themes of process and product, the contributors investigate the productive interplay between the activity of design and the objects that design uses and produces. Chapters span the design disciplines and essays examine the processes by which objects, things, and artifacts are made; the lives of design objects; and things in their cultural contexts. Theoretical discussion is encouraged by in-depth case studies of things themselves. Each chapter includes an informational sidebar per essay and a useful glossary of key terms.